A scheme of economic theory - Shackle, G. L. S. (Cambridge [Eng.] : University Press, 1965)
By their nature and purpose different economic theories make almost opposite assumptions and use entirely different conceptions or aspects of time. These contrasting assumptions, which occur frequently, are essential to the nature of the various theories and cannot therefore be combined into a general theory. Coherence can only be obtained by an explicit scheme in which these theories are ordered to each other. In this book Professor Shackle seeks a single, unified and coherent basis which would serve for all economic theories, particularly in regard to their treatment of time and to the possibility of acquiring the knowledge on which these theories are based. Professor Shackle's examination of these theories and models will be of interest to economists attempting to find coherence in the diversity of economic theory
Includes index
rpm 16/06/2017
Loans
Keywords: Economics